Metrics with unit discs of arbitrary shape. Issue 4 (21st April 2021) - Lynch, Mark
ABSTRACT: In high school, unit discs were all circular. Squares and diamonds were added to the list of shapes in a Real Analysis course and although more bizarre shapes appeared in graduate school, the list of possible shapes didn't appear endless. In this note, we'll show that unit discs can have almost any shape imaginable.